Is Acute Myeloblastic Leukemia in Children Under 2 Years of Age a Specific Entity? A Report from the FRENCH ELAM02 Study Group. Issue 6 (December 2019) - Blais, S.; Boutroux, H.; Pasquet, M.; Leblanc, T.; Fenneteau, O.; Gandemer, V.; Bertrand, Y.; Ducassou, S.; Michel, G.; Nelken, B.; Petit, A.; Cuccuini, W.; et al.
Abstract : Abstract: The clinical and biological characteristics of children under 2 years (infants) with acute myeloid leukemia (AML) are different from those of older children. We aimed to describe the specific characteristics of this population and the potential factors that influence the prognosis. We analyzed data concerning 438 children with newly-diagnosed AML treated in the ELAM02 protocol between March 2005 and December 2011, of which 103 were under 2 years old at diagnosis. The evaluation criteria were overall survival (OS) and event-free survival (EFS) of infants vs older children. The clinical and biological features were secondary criteria. Infants presented more frequent extra-medullary presentation than older children. They had a significantly higher proportion of skin lesions and central nervous system involvement (15% vs 3%, p < 0.0001 and 26% vs 12%, p = 0.0005, respectively). The global incidence of KMT2A rearrangements was nearly 55% for infants vs 11% for older children (p < 0.0001). Median 5-year OS was 70.4% for infants vs 71.4% for older children (p = 0.83). Five-year EFS was 67% for infants vs 58% for older children (p = 0.27). Infants with AML represent a cohort of patients with specific clinical and biological features. These remarkable differences had no significant impact on their outcome in the ELAM02 protocol.